Women's Perspectives on a Reproductive Health Services Screening Question: An Alternative to Pregnancy Intention Screening - Silpa Srinivasulu; Meredith G. Manze; Heidi E. Jones (Mary Ann Liebert, 2022)
Background: Current efforts to integrate reproductive health care into primary care in the United States involve assessing pregnancy intentions and reproductive goals, which are often not meaningful or attainable for some. Alternatively, we designed a reproductive health services-based screening question: ?Can I help you with any reproductive health services today, such as preventing pregnancy or planning a healthy pregnancy?? In this study, we describe women's interpretations of this question as part of a larger study, exploring perspectives on reproductive health care quality in primary care. Materials and Methods: We utilized a third-party research firm to recruit New York women of reproductive age (18?45), who visited a primary care provider in the past year. We conducted five focus groups and eight interviews (N?=?30). Semistructured guides queried participants on interpretations of the screening question and preferences for raising reproductive health concerns during a primary care visit. We employed inductive thematic analysis. Results: Participants interpreted the question as offering contraception or pregnancy counseling and care, although younger participants also understood it as offering sexual and reproductive health services broadly. Participants also connected the question with discussions about their ability to conceive. Some participants described experiences with provider assumptions and implicit bias. Tensions emerged around accepting primary care as a setting for reproductive health due to a perceived lack of specialized training. Conclusions: Participants interpreted the screening question as intended, indicating face validity. Primary care settings should increase patients' awareness of reproductive health service availability, such as by routinely introducing a services-based screening question.